Democracy in the mines. Some documents of the controversy on mines nationaliation up to the time of the Sankey Commission. Selected & ed. K. Coates, with a chapter introd. by A Gottschalk (Spokesman Books, 1974)
Publ. by The Bertrand Russell Peace Foundation.